A Mixed-Methods Investigation of a Rape Crisis Line Volunteer Counselling Program - Louw, Alyssa (Université d'Ottawa / University of Ottawa, 2017)
Rape crisis counsellors play a central role in frontline service delivery to sexual violence (SV) survivors, yet their training has received scarce research attention. To fill this gap, this dissertation presents three studies that sequentially examine a volunteer-based rape crisis line (CL) training program. The first study is an evaluability assessment (EA) that assesses the readiness of a community CL training program for research; the second study quantitatively examines the outcomes of the CL training program; and the third study qualitatively investigates the rape crisis counsellors’ training and practice experiences. Data was gathered from a local Rape Crisis Centre (RCC), and a total of 52 women participated in the research. Two-way mixed factorial ANOVAs were used to analyze the quantitative data, and a general inductive approach (Thomas, 2006), informed by a feminist, empowerment perspective (Nagy Hesse-Biber & Yaiser, 2004) was used to analyze the qualitative data. The EA demonstrated that the CL training program was primarily intended to develop volunteers’ basic counselling skills, suicide intervention skills, and feminist attitudes and beliefs. Based on analyses of the EA data, the program was determined to be evaluable. The second study indicated that following the training, the volunteers’ counselling self-efficacy improved, whereas their suicide intervention skills did not change. Volunteers had strong pre-existing feminist attitudes and beliefs that also did not change. The third study revealed several themes that elucidated the program’s processes and outcomes, such as the volunteers’ perception that after the training they gained basic counselling skills, and an increased knowledge of feminism, yet felt unprepared to respond to suicidal callers. Due to their routine interactions with SV survivors and systems, the volunteers also began to perceive SV as a widespread, systemic problem. A thematic analysis of results across studies, and implications of the findings on anti- violence practice and policy are discussed.
Keywords: Crisis Line Training; Evaluation; Feminist Counselling; Violence Against Women